Investigation of an active noise control system to reduce the noise emitted by an industrial stack - André L’Espérance; Martin Bouchard; Bruno Paillard; Jean-Claude Dubé (Canadian Institute of Mining, Metallurgy and Petroleum, 1997)
"A precise analysis of the noise emitted by an aluminum plant has shown that one of the main sources of noise is the noise emitted by an exhaust stack 40 m high and 1.8 m diametre, emitting a pure tone at 320 Hz. Because a classical cost effective solution is not available for this source, active noise control (ANC) solution was investigated.Commonly available ANC systems, how-ever, are not applicable to the chimney considered because the diameter of the stack (f) is too important compared to the wave length(?)of the frequency to control. In fact, until now, active noise control (ANC) has been successfully used to reduce the acoustical energy emitted at the end of ducts in the case of plane wave propagation, i.e. ?/f< 1.7 [1,4].When f> ?/1.7, high order modes propagate in the duct and a single canal active noise control system is not sufficient.This paper presents an ANC system developed to control higher modes in a circular duct. The controller used is based on a multiple-input, multiple-output adaptive filtered X-LMS and allows up to 11 error micro-phones and controls sources. The system has been used in a laboratory on a finite duct of3.5 m long and 0.30 m diameter which corresponds to the same ratio ?/f for the real stack. The efficiency of the system with different numbers and location of control sources and errors sensors has been analyzed. Noise reduction of 15 dB(A) could be obtained with some configurations. Actually, the system is being considered for installation on the real chimney stack."